Corporate Social Responsibility and Pharmacy Customer Loyalty: The Mediating Roles of Brand Awareness and Brand Trust - Lina Budiarti; Sri Hartini (Golden Ratio of Mapping Idea and Literature Format, 2026)
Customer loyalty has become a strategic priority for pharmacy service providers due to increasing competition and rising customer expectations for socially responsible healthcare services. While Corporate Social Responsibility (CSR) has been widely recognized as an important strategy for enhancing organizational performance, the mechanisms through which CSR fosters customer loyalty in pharmacy services remain insufficiently explored. This study aims to develop a conceptual framework explaining the role of CSR in enhancing pharmacy customer loyalty through the mediating roles of brand awareness and brand trust. Drawing upon Stakeholder Theory and Relationship Marketing Theory, this paper synthesizes relevant literature on CSR, branding, trust, and customer loyalty within healthcare and service contexts. The proposed framework suggests that CSR initiatives, including community health programs, health education, medication counseling, and preventive healthcare campaigns, strengthen customer loyalty by increasing brand awareness and reinforcing brand trust. This study contributes to the marketing and healthcare literature by integrating these constructs into a comprehensive conceptual model specifically tailored to pharmacy services. The framework also provides practical insights for pharmacy managers seeking to improve long-term customer relationships through socially responsible business practices and offers directions for future empirical research.